Towards a fossil fuel non-proliferation treaty. (13th September 2020) - Newell, Peter; Simms, Andrew
ABSTRACT: A new approach is needed to tackle the climate crisis, in which the long overlooked supply-side of fossil fuels takes centre stage. A crucial aspect of this is the need for international agreements and law to effectively and fairly leave large swathes of remaining fossil fuels in the ground. Towards that end, we make the case for a Fossil Fuel Non-Proliferation Treaty (FF-NPT) to deal with emissions at source. Having explained the need for such a treaty, we propose overall aims, and both a process and principles for the sequencing of efforts across fuel types and regions based on equity and justice. We discuss the form an FF-NPT could take, as well as some of the key challenges it would have to overcome. We suggest strategies for overcoming key challenges in relation to reserves in developing countries, questions of the just transition, and incentives for countries to sign up to such a treaty. Key policy insights The supply-side of fossil fuels should occupy a central place in collective efforts to address climate change. A proposed new Fossil Fuel Non-Proliferation Treaty (FF-NPT) could help to keep large swathes of fossil fuels in the ground, effectively and fairly. A process towards this end could start with an assessment of existing reserves, as well as agreement on the principles for the sequencing of production phase-down targets across countries and fuel types, with the aim of aligning fossil fuel use with the Paris Agreement's 1.5°C warming threshold. Strategies to advance the proposed FF-NPT will have to recognize current and historical exploitation of fossil fuel reserves, provide alternative ways of meeting the development needs of the poorest countries without fossil fuels, and include credible systems of monitoring and compliance to induce trust and cooperation.